The Talk Test as a measurement of exercise intensity in children - Heim, Makayla Jade (My University, 2019)
The aim of this study was to identify the replicability of the Talk Test as an indicator of exercise intensity in children. This study specifically looked at whether the TT could be used as a measurement of exercise intensity in children from age nine to 12. Ten children were recruited to perform the study. Subjects completed two visits at the laboratory. The first visit was to familiarize the child with equipment and complete an exercise test using the TT. The second was completing a maximal exercise test performed on a motorized treadmill while measuring respiratory gas exchange. The gas exchange test was used to measure each subject's ventilatory threshold (VT). Results from the last positive (LP), equivocal (EQ), and negative (NEG) stage of the TT were compared to VT. There were no differences between VO2 at VT during any of the TT stages. HR at VT was significantly different compared at the NEG stage of the TT (p<.05). RPE was significantly different than RPE at VT compared at NEG and LP stage of the TT (p<.05). There were no significant differences when comparing the previous data to the current data. Specifically, there was no significant difference between VO2 and TT stages when comparing the Giddings (2018) data and the current data. We concluded that children that are exercising to a point where it is uncomfortable to speak are exercising below their VT. We are confident that the replicability of the TT is an adequate tool to support the TT as a valid measure of exercise intensity in children.
Keywords: Exercise -- Physiological aspects; Exercise for children; Kinesiology